Conductive Ti3C2 and MOF-derived CoSx boosting the photocatalytic hydrogen production activity of TiO2. Issue 14 (13th March 2019) - Zhao, Jia-Hui; Liu, Ling-Wang; Li, Kui; Li, Tao; Liu, Fu-Tian
Abstract : We report a novel TiO2 nanocrystals photocatalyst confined by ZIF-67-templated porous CoS x, with conductive Ti3 C2 boosting the transport efficiency of the charge carriers. Abstract : Design and synthesis of high-efficiency and low-cost photocatalysts is essential for converting solar energy into clean hydrogen energy. Herein, we report a novel TiO2 nanocrystal photocatalyst confined by ZIF-67-templated porous CoS x, with conductive Ti3 C2 boosting the transport efficiency of the charge carriers. TiO2 –CoS x and TiO2 –Ti3 C2 –CoS x exhibit a photocatalytic H2 -production activity 2.8 and 5.8 times larger than that of pristine TiO2, respectively, because of the existence of the highly porous MOF-templated CoS x hydrogen evolution reaction cocatalyst and highly conductive Ti3 C2 . This study will provide a practical reference for the design and preparation of efficient photocatalysts with high transport and utilization efficiency of charge carriers.